DETERMINANTES SOCIAIS DA TUBERCULOSE EM RELAÇÃO AO DESFECHO EM 7 CAPITAIS BRASILEIRAS - Ferreira, Hugo Silva (2021)
Objective: To evaluate the Social Determinants of Tuberculosis in relation to the outcome in 7 Brazilian capitals between March 1, 2014 to April 30, 2017, monitoring patients during the treatment of Tuberculosis. Methods: This is an observational study, with a concurrent (prospective) cohort, in the following capitals: Fortaleza - CE, Manaus - AM, Porto Alegre - RS, Recife - PE, Salvador - BA, São Paulo - SP and Vitória - ES. Patients answered questionnaires and interviews by professionals from the Health Unit itself in three moments: at diagnosis, in the second month of treatment and in the sixth month of treatment. In the second and sixth month of treatment samples of sputum smear and culture were collected. 03ml of blood were collected to check blood glucose and if there was HIV infection. This is a quantitative, descriptive and analytical research, carried out using the database of the study entitled “Analysis of the independent effect of social support on adherence and success rates for the treatment of Tuberculosis in Brazilian capitals” funded by the Ministry of Health. analysis of the epidemiological profile of the patients, the absolute and relative frequency of the variables was calculated, the P-value between the variables and the cure and non-cure outcome were calculated. A multivariate and hierarchical logistic regression model was used to test the association of the outcome variable with the Social Determinants of Tuberculosis. Results: In the first two analyzes, 1253 patients participated, in the third phase with multivariate logistic regression, participants with incomplete data were excluded, and 548 participants were analyzed, where the determinants that had an influence on the healing outcome were observed were: age, income family and have garbage collection. Conclusions: It was found that Social Determinants are directly related to the outcome of Tuberculosis treatment.